Vision and safety welder helmet / Faiz Syazwan Hishamudin and Nor Asma Hafizah Hadzaman - Hishamudin, Faiz Syazwan; Hadzaman, Nor Asma Hafizah (2023)
This innovation report presents a comprehensive study on the development and commercialisation of the vision and safety welder helmet, focusing on safety, comfort, and cutting-edge technology integration. The research addresses key questions and objectives to advance welding safety and efficiency. Investigating advanced technology for the shotcrete method, the study explores its application in designing the vision safety welder helmet. Additionally, it assembles and effectively demonstrates a simulation of the helmet while exploring marketability strategies. The primary aim is to create a vision and safety welder helmet surpassing current safety standards, providing enhanced user comfort. Research objectives guide the project, encompassing innovative helmet design, simulation assembly, performance demonstration, and market evaluation. Employing various research methodologies, including design exploration, engineering simulations, user testing, market research, and marketing strategy development, the helmet integrates advanced vision technology, auto-darkening lenses, and ergonomic headgear to enhance safety and productivity. The assembled simulation effectively showcases the helmet’s performance, demonstrating seamless welding and non-welding state transitions and overall effectiveness in various welding processes and environments.